Mercury Isotopes in Shale Gas From Wufeng-Longmaxi Shale Formation of Sichuan Basin, Southern China: A Preliminary Investigation - Tang, Shunlin; Ding, Yuxiang; Zhu, Guangyou; Feng, Xinbin; Zhang, Huaishun; Li, Penggao (Frontiers in Earth Science, 2022)
A series of investigations have been conducted concerning the study of traditional stable isotopes and rare gas stable isotopes in natural gas. However, little is known regarding non-traditional stable isotopes of mercury in natural gas, especially in the development and utilization of shale gas in recent years. In fact, the presence of mercury in natural gas (including shale gas) provides a basis for research on mercury isotopes. Mercury was extracted from shale gas at the Wufeng-Longmaxi Formation in the YS108 block of the Zhaotong National shale gas demonstration area in the Sichuan Basin by using an acid potassium permanganate solution, followed by the analysis of mercury content and stable isotope composition. The mercury content in the marine shale gas at the Wufeng-Longmaxi Formation ranged from 171 to 2,906 ng/m3, with an average of 1,551.08 ± 787.08 ng/m3 (n = 37, 1 SD). The Δ199Hg values of mercury stable isotopes range from 02‰ to 0.39‰, with an average of 22‰ ± 0.08‰ (n = 37, 1 SD); the δ202Hg values range from −1.68‰ to −0.04‰, with an average of −0.87‰ ± 0.31‰ (n = 37, 1 SD), which are significantly different from the Δ199Hg and δ202Hg information of coalbed gas, but similar to the Δ199Hg and δ202Hg information of terrestrial oil-type gas and the Δ199Hg in the main hydrocarbon-forming organic matter of lower organisms such as algae (t-test, p > 0.05). This indicates that terrestrial target strata with abundant algae or strata with positive Δ199Hg are the target strata for the exploration of terrestrial oil and gas.